Ecological anatomy of the wood of two Mexican taxa of the genus Mimosa (Leguminosae-Mimosoideae) - Montaño-Arias, Susana Adriana; Camargo-Ricalde, Sara Lucía; Grether, Rosaura; Díaz-Pontones, David (Instituto de Ecología, A.C., 2017)
Background and Aims: Eco-anatomical studies enable the estimation of the response of taxa to different environmental factors. Considering the biological and ecological relevance of the genus Mimosa, the adaptive possible responses of two endemic Mexican taxa were estimated, M. aculeaticarpa var. aculeaticarpa y M. luisana, through the eco-anatomical analysis of their wood, in order to evaluate their resistance and tolerance to changes in precipitation.Methods: Three trees of similar size and coverage per taxon, were collected. Wood cubes of 1 × 1 cm were cut and softened by boiling. Transverse, tangential and radial sections, 20 µm in thickness were made. Samples were stained with fast safranin-green and mounted in synthetic resin. The description and the analysis of anatomical wood features were based on the nomenclature proposed by the IAWA.Key results: Mimosa aculeaticarpa var. aculeaticarpa presents ring-porosity, while M. luisana is characterized by diffuse porosity. Mimosa aculeaticarpa var. aculeaticarpa shows vessels with medium tangential diameter in early-wood, and small ones in late-wood, whereas M. luisana presents vessels with small tangential diameter. Both have simple perforation plates, bordered, alternate and small intervessel pits, and vestured ones in M. luisana. Mimosa aculeaticarpa var. aculeaticarpa mainly has axial paratracheal vasicentric parenchyma, while in M. luisana, it is vasicentric and unilateral. In M. aculeaticarpa var. aculeaticarpa, rays are uniseriate, and in M. luisana, they are biseriate. Fibers are of short length, fine diameter and thick wall. The highest indexes of vulnerability (VI) and of mesomorphy (MI) were found in M. aculeaticarpa var. aculeaticarpa (4.05 y 729.05, respectively), indicating that this taxon is the most vulnerable to drought, while the lowest values of both VI and MI corresponded to M. luisana (1.42 and 226.71, respectively), suggesting that this taxon is more resistant to drought.Conclusions: It is proposed that M. aculeaticarpa var. aculeaticarpa is suitable for restoring mesic sites and M. luisana for dry environments.